2002
DOI: 10.1074/jbc.m207345200
|View full text |Cite
|
Sign up to set email alerts
|

Concanamycin A, the Specific Inhibitor of V-ATPases, Binds to the Vo Subunit c

Abstract: Vacuolar-type ATPases (V-ATPases) 1 are complex, heteromultimeric proteins consisting of a peripheral, catalytic V 1 complex and a membrane bound, ion translocating V o complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
247
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 256 publications
(260 citation statements)
references
References 36 publications
11
247
0
2
Order By: Relevance
“…These 'other' inhibitors removed only about 20% of the total ATPase activity, even at relatively high inhibitor concentration. Di-cyclohexyl-carbodiimide, which inhibits proton translocation also in the related F-ATPase (see, e.g., (Kopecky et al 1981;Kopecky et al 1982;Kopecky et al 1983;Hermolin and Fillingame 1989;Wada et al 2000)), was more potent, but the most potent inhibitors were, as expected, concanamycin A and bafilomycin, even when applied at the lowest concentrations (Bowman et al 1988;Drose et al 1993;Gagliardi et al 1999;Huss et al 2002;Dixon et al 2008). In this system, and under the present conditions, these inhibitors removed ~60% of the total ATPase activity, which varied to some extent from isolation to isolation.…”
Section: Atpase Activity Assaysupporting
confidence: 53%
See 3 more Smart Citations
“…These 'other' inhibitors removed only about 20% of the total ATPase activity, even at relatively high inhibitor concentration. Di-cyclohexyl-carbodiimide, which inhibits proton translocation also in the related F-ATPase (see, e.g., (Kopecky et al 1981;Kopecky et al 1982;Kopecky et al 1983;Hermolin and Fillingame 1989;Wada et al 2000)), was more potent, but the most potent inhibitors were, as expected, concanamycin A and bafilomycin, even when applied at the lowest concentrations (Bowman et al 1988;Drose et al 1993;Gagliardi et al 1999;Huss et al 2002;Dixon et al 2008). In this system, and under the present conditions, these inhibitors removed ~60% of the total ATPase activity, which varied to some extent from isolation to isolation.…”
Section: Atpase Activity Assaysupporting
confidence: 53%
“…Our data is compatible only with a single binding site per monomeric enzyme. Since concanamycin A most likely binds to intramembranous subunits Whyteside et al 2005;Bowman et al 2006;Dixon et al 2008), the present result suggests that an interaction with a single subunit c is not sufficient for concanamycin A binding: it either binds to more than one subunits or it binds to either subunit a, c' or c" (Huss et al 2002), of which there are only one copies in the structure, although its interaction with the lobster c ring and other recent data Bowman et al 2006;Dixon et al 2008) argue against c' and c'' being the binding sites. The accuracy of our approach could be further improved by adding more points to the inhibitor titration curve.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This similarity in biological activity already suggested that 4, like other members of the archazolid family, should target V-ATPases. Indeed, by using established procedures it was shown that the purified V-ATPase holoenzyme from the midgut of the tobacco hornworm was inhibited with an IC 50 value of 1.2 mmol/mg enzyme [7,11,12]. Thus, 4 is much less inhibitory than 1 and 2 with an IC 50 value of 0.6 nmol/mg enzyme.…”
mentioning
confidence: 99%